Female volatiles as sex attractants in the invasive population of Vespa velutina nigrithorax. (November 2019) - Cappa, Federico; Cini, A.; Pepiciello, I.; Petrocelli, I.; Inghilesi, A.F.; Anfora, G.; Dani, F.R.; Bortolotti, L.; Wen, P.; Cervo, R.
Graphical abstract: Highlights: Venom volatiles did not differ between female castes in Vespa velutina nigrithorax . Males were not attracted by venom volatiles. Sternal gland secretion differed between female castes. Males were attracted by the females' sternal gland secretion. Abstract: Due to its huge invasion potential and specialization in honeybee predation, the invasive hornet Vespa velutina nigrithorax represents a high-concern species under both an ecological and economical perspective. In light of the development of specific odorant attractants to be used in sustainable control strategies, we carried out both behavioural assays and chemical analyses to investigate the possibility that, in the invasive population of V. velutina nigrithorax, reproductive females emit volatile pheromones to attract males, as demonstrated in a Chinese non-invasive population. We focused on the secretions produced by sternal and venom glands; because of the volatility and complexity of their composition, both of them could potentially allow an attraction and a species-specific response, decreasing therefore non-target species by-catches. Results of chemical analyses and behavioural assays showed that venom volatiles, although population-specific, are unlikely candidates as male attractants since they do not differ in composition or in quantity between reproductive females and workers and do not attract males. Conversely, sternal gland secretion differs between female castes for the presence of some ketoacids exclusive of gynes already reported as sex pheromones for the non-invasive subspecies V. velutina auraria . Despite such a difference, males are attracted by the sternal gland secretion of both workers and gynes. These results provide a first step to understand the reproductive biology of V. velutina nigrithorax in its invasive range and to develop effective and sustainable management strategies for the species.